On Ore from the Dashuigou Tellurium Deposit, Tibet Plateau, Southwest China - Yin, Jianzhao; He, Dongsheng; Yin, Yuhan; Shi, Hongyun; Xiang, Shoupu (European Journal of Applied Sciences, 2022)
The Dashuigou independent tellurium deposit is the first and only tellurium deposit discovered in the world so far. Studies have shown that tellurium will be the best replacement for the next generation of green batteries. Therefore, a comprehensive study of this unique deposit has both theoretical and practical significance. This paper studies both the physical and chemical properties of the ore in the Dashuigou independent tellurium deposit, and provides a theoretical basis for mining and ore processing. The ore of the Dashuigou tellurium mine is composed of more than 30 kinds of minerals including carbonates, silicates, sulfides, oxides, tellurides, and native element minerals. The ore contains Te between 0.01% and 34.58%. The ore also contains beneficial elements such as Bi, Au, and Ag that can be comprehensively utilized. The main types of ore are massive, veined, and disseminated.